Analisis Pengaruh Pelatihan Resusitasi Jantung Paru RJP Dewasa terhadap Retensi Pengetahuan dan Ketrampilan RJP pada Mahasiswa Keperawatan di Yogyakarta - Widyarani, Linda (Jurusan Keperawatan FIKES UNSOED, 2017)
Cardiac arrest is a major public health problem affecting thousands of individuals each year in both out-of-hospital and in-hospital setting. High quality of cardiopulmonary resuscitation (CPR) provide return of spontaneous after cardiac arrest, but majority of nursing students feel unconfident to practice CPR. The aim of the study was to assess the effect of CPR training program on knowledge and practices of nursing students in Yogyakarta. The study design was quasi-experimental and one group pretest – posttest design. A questionnaire was applied to the students before CPR training, then the student were informed about adult CPR by the researchers and all of the students practice CPR on a Resusci-Anne manikin. One months after this training the same questionnaire and skills checklist of CPR were applied. Sixty five students of nursing participated in this study. This study show CPR training significantly positive impact cognitive and skills performance in nursing students. While the average CPR knowledge score of these students was 44,43%, before CPR training, this average increased to 89,64% after CPR training and decreased to 77,54% after one month CPR training. Skill score of the students one month after the CPR skill training was 70,61%. Nursing students tend to forget theoretical and applied CPR training after one month. Hence there is a need for continuous CPR training and education and repeating the skills at regular intervals ever after they have graduated to ensure sustainability in the CPR skills.